2002
DOI: 10.1159/000064469
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms and Kinetics of Bowman’s Epithelial-Myofibroblast Transdifferentiation in the Formation of Glomerular Crescents

Abstract: Background: We investigated the mechanisms and kinetics of Bowman’s epithelial-myofibroblast transdifferentiation in the formation of glomerular crescents. Methods: Crescentic glomerulonephritis was induced by i.v. injection of rabbit anti-rat glomerular basement membrane antiserum in WKY rats. Results: Cellular crescents (83.5% of glomeruli) were first observed at day 7 after disease induction. Immunostaining of alpha-smooth muscle actin (alpha-SMA), as a marker for the myofibroblast phenotype, was found in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 17 publications
1
31
0
Order By: Relevance
“…Thus, toxic or pathological stimuli and͞or the presence of stem cells may explain the appearance of hepatocytes in the rodent pancreas in response to a copper-deficient diet (24,25) or insular overexpression of keratinocyte growth factor (26). Similar mechanisms may be responsible for transdifferentiation of hepatic to exocrine pancreatic cells after treatment with polychlorinated biphenils (27) and transplantation of pancreatic epithelial cells (28), as well as for the conversion of kidney tubular epithelial cells into fibroblasts during experimental fibrosis (29) and of Bowman's capsule epithelial cells into myofibroblasts during experimental glomerulonephritis (30). On the other hand, the term ''transdifferentiation'' can hardly be applied to the differentiation of embryonic endothelial cells into cardiomyocytes in various experimental conditions (31) or to the switch from muscular to adipose phenotype in skeletal muscle under disruption of Wnt signaling (32).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, toxic or pathological stimuli and͞or the presence of stem cells may explain the appearance of hepatocytes in the rodent pancreas in response to a copper-deficient diet (24,25) or insular overexpression of keratinocyte growth factor (26). Similar mechanisms may be responsible for transdifferentiation of hepatic to exocrine pancreatic cells after treatment with polychlorinated biphenils (27) and transplantation of pancreatic epithelial cells (28), as well as for the conversion of kidney tubular epithelial cells into fibroblasts during experimental fibrosis (29) and of Bowman's capsule epithelial cells into myofibroblasts during experimental glomerulonephritis (30). On the other hand, the term ''transdifferentiation'' can hardly be applied to the differentiation of embryonic endothelial cells into cardiomyocytes in various experimental conditions (31) or to the switch from muscular to adipose phenotype in skeletal muscle under disruption of Wnt signaling (32).…”
Section: Discussionmentioning
confidence: 99%
“…Isolated glomeruli were plated onto type I collagen-coated 10-cm plates (at a concentration of 6 glomeruli/cm 2 ) and maintained in medium containing 5% FBS. Cellular outgrowths were observed daily by an inverted light microscope.…”
Section: Establishing Immortalized Mouse Pecmentioning
confidence: 99%
“…PEC make up a large part of glomerular crescents in certain forms of ANCA and non-ANCA-related glomerulonephritis. Moreover, in disease, they express several cytokines and chemokines, such as TGF-␤1, 1 PDGF-B, 2 and CTGF, 3 and more recent studies suggested that they might also be precursors to podocytes. 4 Several animal models of glomerulonephritis characterized by PEC proliferation have enhanced our understanding of these cells in disease.…”
mentioning
confidence: 99%
“…These changes are often referred to as cellular transformation or transdifferentiation, and reflect cell-type phenotypic plasticity. Phenotypic plasticity is also observed or has been postulated in pathological tissues [5,6], including neoplastic disease [5]. Here, within any given tumor-type (for example, lymphoma, carcinoma, melanoma, sarcoma) we are aware that a diversity of differentiation is often found, and this can also be regarded as an expression of phenotypic plasticity.…”
mentioning
confidence: 99%